Impact of prenatal exercise on maternal harms, labour and delivery outcomes: a systematic review and meta-analysis. Issue 2 (18th October 2018) - Davenport, Margie H; Ruchat, Stephanie-May; Sobierajski, Frances; Poitras, Veronica J; Gray, Casey E; Yoo, Courtney; Skow, Rachel J; Jaramillo Garcia, Alejandra; Barrowman, Nick; Meah, Victoria L; Nagpal, Taniya S; Riske, Laurel; et al.
Abstract : Objective: To perform a systematic review of the relationships between prenatal exercise and maternal harms including labour/delivery outcomes. Design: Systematic review with random effects meta-analysis and meta-regression. Datasources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies) if they were published in English, Spanish or French and contained information on the population (pregnant women without contraindication to exercise), intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise), comparator (no exercise or different frequency, intensity, duration, volume and type of exercise, alone ["exercise-only"] or in combination with other intervention components [e.g., dietary; "exercise + co-intervention"]) and outcome (preterm/prelabour rupture of membranes, caesarean section, instrumental delivery, induction of labour, length of labour, vaginal tears, fatigue, injury, musculoskeletal trauma, maternal harms (author defined) and diastasis recti). Results: 113 studies (n=52 858 women) were included. 'Moderate' quality evidence from exercise-only randomised controlled trials (RCTs) indicated a 24% reduction in the odds of instrumental delivery in women who exercised compared with women who did not (20 RCTs, n=3819; OR 0.76, 95% CI 0.63 to 0.92, I 2 = 0 %). The remaining outcomes were not associated with exercise. Results from meta-regression did not identify a dose–response relationship between frequency, intensity, duration or volume of exercise and labour and delivery outcomes. Summary/conclusions: Prenatal exercise reduced the odds of instrumental delivery in the general obstetrical population. There was no relationship between prenatal exercise and preterm/prelabour rupture of membranes, caesarean section, induction of labour, length of labour, vaginal tears, fatigue, injury, musculoskeletal trauma, maternal harms and diastasis recti.